Etnis Tionghoa dan Konflik Sosial di Surakarta: Analisis Historis Kerusuhan 1998 - Moch Akbar Maulana (Perkumpulan Program Studi Sejarah Se-Indonesia, 2026)
This study examines the May 1998 riots in Surakarta by focusing on their causes, dynamics, and impacts on the Chinese Indonesian community. The monetary crisis that began in late 1997 triggered economic instability, mass unemployment, and social unrest, which escalated into large-scale riots. The Chinese Indonesians became the main targets of looting, arson, and physical as well as sexual violence, leaving deep psychological trauma and significant material losses. This research employs historical methodology through four stages: heuristics, source criticism, interpretation, and historiography. Primary sources consist of local newspapers (Solopos and Suara Merdeka), supported by secondary sources such as books and academic journals. The findings reveal that the Surakarta riots were not merely spontaneous incidents but were closely linked to the discriminatory policies of the New Order, socioeconomic disparities, and the state’s failure to protect minority groups. After the riots, the Chinese community faced long-term challenges, including loss of security, distrust toward the government, and economic collapse. However, community-based reconciliation efforts, such as those in Surakarta’s Chinatown, played a role in rebuilding social harmony. This study highlights the importance of both structural and cultural approaches in preventing the recurrence of similar ethnic conflicts in the future.